UTILIZATION OF COAL ACTIVATED CARBON AS ADSORBENT AMMONIUM WITH THE HIGH CONCENTRATION - Ika Monika; Suganal Suganal; Fahmi Sulistyohadi (Puslitbang tekMIRA, 2015)
Ammonium adsorption process carried out by batch system, with making 208-233 mg/L concentration of am- monium solution. In the adsorption batch systems, particle size of activated carbon -8 + 12 mesh and -16 + 20 mesh was added into 200 ml ammonium solution with the weight of 20, 40, 60 and 80 g, and a contact time respectively 30, 60, 120, 180 and 1440 minutes (24 hours). During the adsorption, stirring to optimize adsorp- tion is conducted regularly. The activated carbon used in this research consist of two types are coal based activated carbon and coconut shell activated carbon. Coal activated carbon has a surface area 196.7 m2/g and 643.0 m2/g. While coconut shell activated carbon has a surface area of 59.6 m2/g and 985.9 m2/g. Results of the adsorption process showed that coal activated carbon with a surface area of 643, 0 m2/g have the same capability ammonium adsorption with coconut shell activated carbon with a surface area of 985.9 m2/g. These results showed that a both types of activated carbon can be used optimally for the removal ammonium with percentage of adsorption reaches more than 90%.